A catalog of new Blazar candidates with Open Universe by High School students. Issue 1 (1st February 2023) - Fronte, L.; Mazzon, B.; Metruccio, F.; Munaretto, N.; Doro, M.; Giommi, P.; Viale, I.; Barres de Almeida, U.
Abstract: Blazars are active galactic nuclei whose ultra-relativistic jets are co-aligned with the observer direction. They emit throughout the whole e.m. spectrum, from radio waves to VHE gamma rays. Not all blazars are discovered. In this work, we propose a catalog of new highly probable candidates based on the association of HE gamma ray emission and radio, X-ray an optical signatures. The relevance of this work is also that it was performed by four high school students from the Liceo Ugo Morin in Venice, Italy using the open-source platform Open Universe in collaboration with the University of Padova. The framework of the activity is the Italian MIUR PCTO programme. The success of this citizen-science experience and results are hereafter reported and discussed.